Project management in practice - Meredith, Jack R.; Shafer, Scott M. (John Wiley & Sons, 2021)
The use of projects and project management continues to accelerate in our global societies. With the addition of Agile, project management is now also being used for dynamic, "quasi" projects, initiatives where the scope, budget and deadline are changing constantly.